2018
DOI: 10.1038/s41571-018-0085-0
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing in prostate cancer

Abstract: Androgen receptor (AR) splice variants (AR-Vs) have been implicated in the development and progression of metastatic prostate cancer. AR-Vs are truncated isoforms of the AR, a subset of which lack a ligand-binding domain and remain constitutively active in the absence of circulating androgens, thus promoting cancer cell proliferation. Consequently, AR-Vs have been proposed to contribute not only to resistance to anti-androgen therapies but also to resistance to radiotherapy in patients receiving combination th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
135
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(136 citation statements)
references
References 132 publications
1
135
0
Order By: Relevance
“…We subsequently tested this postulate using spliceosome inhibitors. Several microbial products, including Pladienolide B and its derivative E7107 have been shown to bind and inhibit the SF3B1 complex and manifest anti-cancer activities (12,20). The E7107 compound represented the first-in-class spliceosome inhibitor that underwent phase I clinical trial (66).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We subsequently tested this postulate using spliceosome inhibitors. Several microbial products, including Pladienolide B and its derivative E7107 have been shown to bind and inhibit the SF3B1 complex and manifest anti-cancer activities (12,20). The E7107 compound represented the first-in-class spliceosome inhibitor that underwent phase I clinical trial (66).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of AR variants, ARv7 in particular, have implicated splicing dysregulation in PCa resistance to ADT/Enza (20). Recently, splicing factor HNRNPL was identified as a dependency for LNCaP cells (70) and SFPQ (i.e., PSF) was reported to promote AR splicing and CRPC cell survival (71).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that AR mRNA and protein were unchanged in MED19 LNCaP cells compared to control LNCaP cells under androgen deprivation (Fig 3A and 3B). MED19 overexpression also did not induce expression of AR-V7, a constitutively active splice variant of AR lacking the ligand binding domain that can drive androgen independence in prostate cancer (S4 Fig) [32].…”
Section: Resultsmentioning
confidence: 99%